Effect of adding different concentrations of reduced glutathione to semen extenders stored at 5C° on the percentage of live sperm and integrity of plasma membrane and acorosome of Awassi rams. - Banana, Husam J. H.; Alkhazreji, Hakem T.A. (Journal of Kerbala for Agricultural Sciences, 2018)
This study was carried out during the period from February 2017 to March 2017, in order to determine the effect of adding different levels of reduced glutathione (antioxidant) to dilute the semen of the Awassi rams and their effect on semen characteristics after cooling at 5C° for five days, Livestock and laboratories affiliated to the Department of Animal Production / College of Agriculture / University of Baghdad in Jadiriyah. In this study, four local awassi rams were used, its ages ranging from 2 to 4 years. Semen were collected by artificial vagina at a rate of one ejaculate/ ram /week, then the semen were mixed (Pooled) to remove the individual differences between the rams and tests were conducted to evaluate the characteristics of fresh semen before the dilution which include color, viscosity, pH, mass motility, individual motility, sperm concentration and the percentage of viable and abnormal sperms. The samples were divided equally on the experimental treatments using TRIS extender and a 1: 10 dilution ratio, which consisted of 3 treatments that’s contain glutathione as follows: T1: control group (Tris diluted). T2: Tris dilute + glutathione (30 mg /100 ml). T3: Tris dilute + glutathione (60 mg / 100 ml). The results indicated that the addition of reduced glutathione (T3) resulted in a high significant (P <0.01) in the characteristics of (the percentage of live sperm, and the ratio of sperm with the plasma membrane integrity at time 96 hours. It was (67.50±2.84, 25.75±0.67, 54.50± 2.39%) respectively. No significant differences were recorded between the treatments in the percentage of sperm with acrosome itegrity. The treatment was (T3) (0.85 ± 90.25%) and the treatment (T2) (0.64 ± 89.50%) compared with the control treatment.